"Candidatus Accumulibacter delftensis": A clade IC novel polyphosphate-accumulating organism without denitrifying activity on nitrate. (15th September 2019) - Rubio-Rincón, F.J.; Weissbrodt, D.G.; Lopez-Vazquez, C.M.; Welles, L.; Abbas, B.; Albertsen, M.; Nielsen, P.H.; van Loosdrecht, M.C.M.; Brdjanovic, D.
Abstract: Populations of " Candidatus Accumulibacter", a known polyphosphate-accumulating organism, within clade IC have been proposed to perform anoxic P-uptake activity in enhanced biological phosphorus removal (EBPR) systems using nitrate as electron acceptor. However, no consensus has been reached on the ability of " Ca. Accumulibacter" members of clade IC to reduce nitrate to nitrite. Discrepancies might relate to the diverse operational conditions which could trigger the expression of the Nap and/or Nar enzyme and/or to the accuracy in clade classification. This study aimed to assess whether and how certain operational conditions could lead to the enrichment and enhance the denitrification capacity of " Ca. Accumulibacter" within clade IC. To study the potential induction of the denitrifying enzyme, an EBPR culture was enriched under anaerobic–anoxic–oxic (A2O) conditions that, based on fluorescence in situ hybridization and ppk gene sequencing, was composed of around 97% (on a biovolume basis) of affiliates of " Ca . Accumulibacter" clade IC. The influence of the medium composition, sludge retention time (SRT), polyphosphate content of the biomass (poly-P), nitrate dosing approach, and minimal aerobic SRT on potential nitrate reduction were studied. Despite the different studied conditions applied, only a negligible anoxic P-uptake rate was observed, equivalent to maximum 13% of the aerobic P-uptake rate. An increase in the anoxic SRT at the expenses of the aerobic SRT resulted in deterioration of P-removal with limited aerobic P-uptake and insufficient acetate uptake in the anaerobic phase. A near-complete genome (completeness = 100%, contamination = 0.187%) was extracted from the metagenome of the EBPR biomass for the here-proposed " Ca. Accumulibacter delftensis" clade IC. According to full-genome-based phylogenetic analysis, this lineage was distant from the canonical " Ca. Accumulibacter phosphatis", with closest neighbor " Ca. Accumulibacter sp. UW-LDO-IC" within clade IC. This was cross-validated with taxonomic classification of the ppk1 gene sequences. The genome-centric metagenomic analysis highlighted the presence of genes for assimilatory nitrate reductase ( nas ) and periplasmic nitrate reductase ( nap ) but no gene for respiratory nitrate reductases ( nar ). This suggests that " Ca. Accumulibacter delftensis" clade IC was not capable to generate the required energy (ATP) from nitrate under strict anaerobic-anoxic conditions to support an anoxic EBPR metabolism. Definitely, this study stresses the incongruence in denitrification abilities of " Ca. Accumulibacter" clades and reflects the true intra-clade diversity, which requires a thorough investigation within this lineage. Graphical abstract: Image 1 Highlights: Long term operation of an A2 O reactor did not result in the acclimatization nor adaptation of a DPAO. The PAO genome of this study did not encode the necessary genes to denitrify from nitrate. Classification of PAO denitrifying activity based on the ppk1 -gene-delineated clades I & II is not valid.